All-Optical OFDM Demultiplexer Based on an Integrated Silicon-on-Insulator Technique - Hai Yu; Hongchen Yu; Hongwei Chen; Minghua Chen; Sigang Yang; Shizhong Xie (IEEE Photonics Journal)
An all-optical orthogonal frequency-division multiplexing (OFDM) demultiplexer based on silicon-on-insulator (SOI) waveguide technology is proposed and experimentally demonstrated. Such an integrated structure performing a discrete Fourier transform (DFT) not only has the advantages of a smaller volume and better stability but can also handle more optical subcarriers by increasing the number of the cascaded Mach–Zehnder interferometer (MZI) stages. An SOI-based eight-channel OFDM demultiplexer has been successfully fabricated with a free spectrum range (FSR) of approximately 64 GHz. Eight-subcarrier optical OFDM signals with non-return-to-zero (NRZ) formats are successfully detected by the proposed demultiplexer after a 30-km fiber-link transmission. The total modulation speed is 64 Gbaud, and the bit error rate (BER) performance of each subcarrier is also measured.